Effects of intravenous clonidine on hemodynamics and plasma cortisol level during laparoscopic urological surgeries in a tertiary care hospital - Ananya Saha; Maitreyee Mukherjee; Sovan Sikdar; Sajib Chatterjee; Arpita Laha (Asian Journal of Medical Sciences, 2022)
Background: Laparoscopic urologic surgeries causes rise in Blood pressure and heart rate. Maintenance of hemodynamics is an essential part of anaesthetic management.